Comparison of Volatile Profile of Moringa oleifera Leaves from Rwanda and China Using HS-SPME - Mukunzi, Daniel; Nsor-Atindana, John; Xiaoming, Zhang; Gahungu, Arthur; Karangwa, Eric; Mukamurezi, Godelieve (Pakistan Journal of Nutrition, 2011)
Moringa oleifera leaf samples from China and Rwanda were used for volatile profile analysis. Volatile compounds were analyzed using the Headspace-Solid Phase Microextraction (HS-SPME)-Gas Chromatography-Mass Spectrometry (GC-MS). A total of 93 volatiles consisting of aldehydes, alcohols, ketones, hydrocarbons, esters, terpenoids and acids were identified. While a total of 61 compounds were contained in the sample from China with acetic acid (12.54% of total volatiles) as the most abundant volatile compound, Rwandan sample contained 59 compounds having hexanoic acid (19.81% of total volatiles) as the most abundant one. Chinese sample showed a higher amount of fat (3.56%) and protein (29.54%) than Rwandan sample fat (3.48%) and protein (25.26%). The ash content was found to be higher in Rwandan sample than in Chinese sample 17.26% and 13.44% respectively. The total polyphenol and total flavonoid contents of Chinese and Rwandan samples were respectively as follow Chinese sample (24.65 mg GAE/g dry weight basis and 39.08 mg Rutin Eq/g dry weight basis) and Rwandan sample (30.01 mg GAE/g dry weight basis; 52.78 mg Rutin Eq/g dry weight basis).